DESAIN SISTEM INFORMASI REKAM MEDIS GUNA MENUNJANG TATA KELOLA KLINIS PELAPORAN INDEKS PENYAKIT DENGAN METODE AGILE - Purwati Hasanah; Yuda Syahidin; Erix Gunawan (INFOKOM (Informatika & Komputer), 2023)
This research aimed to design of outpatient disease index information system using V-Model Method and implementation with visual programming. This research use qualitative research methods with descriptive approach, with data collection techniques based on observation, interview, and literature review. In developing of this information system of outpatient disease index built using waterfall method and Data Flow Diagram (DFD) aids.Problems found in this research are : (1) Data processing was done in hand writing, so the officers took a long time. (2) There was no special system of disease index computerized. (3) Making report of disease index activities manually.The suggestion from writer are : (1) It needs using Standar Operating Prosedur (SOP) of disease index the writer made a draft of Standar Operating Prosedur (SOP) so that indexing activities can run continuously. (2) Adding human resources to manage of outpatient disease index. (3) It’s needs to evaluated the system and training about information system for user.